2022
DOI: 10.1177/20406223221083509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium-glucose cotransporter-2 (SGLT2) inhibitors on serum urate levels in patients with and without diabetes: a systematic review and meta-regression of 43 randomized controlled trials

Abstract: Objectives: Sodium-glucose cotransporter-2 (SGLT2) inhibitors have been found to reduce serum urate in patients with type 2 diabetes mellitus. To evaluate if this effect applies to both patients with and without diabetes, we conducted a systematic review and meta-analysis of SGLT2 inhibitors on serum urate levels in this population. Methods: Four electronic databases (PubMed, Embase, Cochrane and SCOPUS) were searched on 25 September 2021 for articles published from 1 January 2000 up to 25 September 2021, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 84 publications
(81 reference statements)
1
23
0
2
Order By: Relevance
“…One of the potential mechanisms through which SGLT-2 inhibitors in uence the cardiovascular and renal risk might be via reduction of SUA levels in diabetic patients. Corroboratively, in two metaanalysis of 62 and 43 clinical trials, SGLT-2 inhibitors decreased SUA concentrations when baseline uric acid levels were within normal range and this effect was constant over two years [8,11]. In our study, SUA levels were mostly within normal range especially with normal GFR rates and decline in uric acid levels continued during the treatment and was still signi cant at 12th month of therapy.…”
Section: Discussionsupporting
confidence: 66%
“…One of the potential mechanisms through which SGLT-2 inhibitors in uence the cardiovascular and renal risk might be via reduction of SUA levels in diabetic patients. Corroboratively, in two metaanalysis of 62 and 43 clinical trials, SGLT-2 inhibitors decreased SUA concentrations when baseline uric acid levels were within normal range and this effect was constant over two years [8,11]. In our study, SUA levels were mostly within normal range especially with normal GFR rates and decline in uric acid levels continued during the treatment and was still signi cant at 12th month of therapy.…”
Section: Discussionsupporting
confidence: 66%
“…[45][46][47][48] The gout and cardiovascular benefits associated with SGLT2i in these target trial emulations may guide selection of glucose-lowering therapy in patients with T2D who are at risk for (or already have) gout needing a second-line agent after metformin. Several meta-analyses of randomized clinical trials (including those conducted in individuals without T2D) have found that SGLT2i was associated with reduced serum urate levels [16][17][18][19] ; elevated urate is a necessary factor for the development of gout. 20,21,[50][51][52] A central mechanism for the uratelowering effect of SGLT2i is thought to be through increased glycosuria, which in turn competes with soluble urate for GLUT9-mediated reabsorption in the proximal tubule, 53 enhancing urinary urate excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses of randomized clinical trials (including those conducted in individuals without T2D) have found that SGLT2i was associated with reduced serum urate levels; elevated urate is a necessary factor for the development of gout . A central mechanism for the urate-lowering effect of SGLT2i is thought to be through increased glycosuria, which in turn competes with soluble urate for GLUT9-mediated reabsorption in the proximal tubule, enhancing urinary urate excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia is another detrimental factor for endothelial cells, but it also mediates inflammatory response and forms deposits in the kidney, which can cause damage to the tubules. SGLT2i have a decreasing effect on uric acid levels, as shown by two meta-analyses, of which the more recent one by Yip et al in 2022 determined a beneficial effect of SGLT2 inhibition on reducing serum urate concentrations in patients with and without DM [ 78 ]. In 2018, however, Zhao et al found that this effect was abolished in patients with eGFR < 60 mL/min per 1.73 m 2 [ 79 ].…”
Section: Renoprotective Effects Of Sglt2 Inhibitorsmentioning
confidence: 99%